Strategi Hybrid Pengumpulan Zakat di BAZNAS Kabupaten Siak - Mahmuda, Mahmuda; Alhasanah, Erni Juliana (LABATILA : Jurnal Ilmu Ekonomi Islam, 2025)
This study develops a hybrid strategy for zakat collection at BAZNAS Siak by combining traditional channels (UPZ, face‑to‑face services) with digital channels (civil‑servant payroll, QRIS, e‑wallets, bank transfer). A qualitative case study was employed using in‑depth interviews, participatory observation, and documentation, analyzed through a strategic management lens and a weighted SWOT using IFAS–EFAS matrices based on 2022–2024 performance data. Findings indicate traditional channels remain vital for trust building and senior segments, while digital channels enhance efficiency, reach, and transparency; IFAS 2.66 and EFAS 2.53 position the organization in Quadrant I, calling for measured growth. Priority actions include channel orchestration (payroll for routine compliance; QRIS/e‑wallets for on‑demand payments; website for education and receipts), capacity building and assisted‑digital SOPs at UPZ, cross‑channel data integration, and expansion of payroll plus partnerships with Islamic banks/fintechs. The study contributes an implementable hybrid model for zakat institutions operating in low‑tech adoption contexts